Why we write about ourselves : twenty memoirists on why they expose themselves (and others) in the name of literature - Maran, Meredith (Plume, 2016)
"Everything an aspiring memoirist needs to know, in one readable volume, a follow-up to the acclaimed writers' handbook Why We Write For the many amateurs and professionals who write about themselves--bloggers, journal-keepers, aspiring essayists, and memoirists--this book offers inspiration, encouragement, and pithy, practical advice. Twenty of America's bestselling memoirists share their innermost thoughts and hard-earned tips with veteran author Meredith Maran, revealing what drives them to tell their personal stories, and the nuts and bolts of how they do it. Speaking frankly about issues ranging from turning oneself into an authentic, compelling character to exposing hard truths, these successful authors disclose what keeps them going, what gets in their way, and what they love most--and least--about writing about themselves"--